4m=3m+12

Simple and best practice solution for 4m=3m+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4m=3m+12 equation:


Simplifying
4m = 3m + 12

Reorder the terms:
4m = 12 + 3m

Solving
4m = 12 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
4m + -3m = 12 + 3m + -3m

Combine like terms: 4m + -3m = 1m
1m = 12 + 3m + -3m

Combine like terms: 3m + -3m = 0
1m = 12 + 0
1m = 12

Divide each side by '1'.
m = 12

Simplifying
m = 12

See similar equations:

| 2y+4x=56 | | (x+3)(x^2+5x+4)=0 | | 5n^5-5n^4+6n^3-6n^2= | | 5t/7=15 | | -y^2=11 | | 7-5(8x+4)=-2 | | -26+3x=-52+9 | | 2/9s=8 | | 5x-20=12-3x | | 5b-2b-20=3b-10 | | 8+3x=5x+6 | | p(x)=x^2+1 | | mx+nz=p | | Y-9=-6(x-3) | | 5d-5=11 | | h(x)=x/2-1 | | (2x-4)(5x+9)=0 | | X/4=8.7 | | 58=27-g | | 6xy^5+3yx^4+9x^2=0 | | 20-65a-8= | | 4c-3(c-6)=2+2+2c | | F(x)=(x+I)(x-I) | | 20-1=x-3 | | 8(k-6)+58=2(2k+5) | | 11/8(4x−8)−2=11/16(8x−12) | | Z-350=371 | | b-/2=4 | | 5x+2(11-4x)=8(-2t+11) | | 45-x=3 | | 3=(-6/x) | | -2(-2y+1)=-2y+22 |

Equations solver categories